MONTHLY REPORT INFORMATION SYSTEM PROSECUTOR'S INTELLIGENCE FIELD - Alvarizqi Cahya Saputra; Teguh Andriyanto, Rini Indriati, Rina Firliana (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
The intelligence department of the state attorney general's office recapitulates monthly reports on information obtained through the prosecutor's intelligence activities. Each incoming report will be managed using Microsoft Word and saved as a file. But in reality, the management process is a bit hampered because of the many report formats and even the file has the potential to be lost or damaged. The purpose of the research is to develop a monthly report information system in the field of Intelligence to help manage report data and recapitulate monthly reports. In the development of this monthly report information system using the waterfall method. Analysis of system requirements requires communication that aims to understand the software expected by users and the limitations of the software. System design is needed to assist in the system implementation process. The implementation of this information system uses the PHP programming language and uses MySQL as the Database Management System. Testing the system using User Acceptance Testing (UAT), which is to ensure the verification process that what the system does is appropriate for the user. From this research resulted in a web-based information system that can assist in the management of monthly reports in the field of prosecutor's intelligence